أورام الثدي وجراحته والجديد فيه - النقري محمد (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة41 مريضة في قسم أورام الثدي أوديسا الحكومية .تراوح عمر المريضات بين 20-80 سنة . وكانت نتائج التشريح المرضي 33 حالة خبيثة 5 منها سرطان فصيصي و 28 سرطان قنوي غازي, 6 حالات داء ليفي كيسي وحالة واحدة خراج ثدي خضعت كل المريضات للفحوصات الآتية : الفحوصات الشعاعية : 1. ماموغرافي للثديين. 2. صورة بسيطة للصدر. 3. أمواج فوق الصوت للحوض والبطن. 4. ومضان عظام للحالات المشكوك فيها. الفحوص الهرمونية : مستقبلات الإستروجين مستقبلات البروجسترون المشعر السرطاني Hen2 المشعر الورمي CA كان العلاج الجراحي في دراستنا باختيار ما بين الجراحة الجذرية والجراحة الجذرية الواسعة مضافا إليها تصنيف الورم علاج هرموني أو شعاعي أو كليهما معا بحسب الحالة النسيجية واتبع معيار TNM . This Study included 41 patients in the Department of Breast Tumor at Awadessa Public University. The average patient age was between 20-80 years. Histopathology results showed 33 carcinoma cases, 5 of which involved lobular carcinoma, 28 cases represented invasive tubular carcinoma, 6 cases developed fibro-cyst disease, and 1 case breast abscess All patients underwent the following general tests: Radiology Tests 1. Mammography 2. Chest- X- RAY 3. Abdomen & pelvic USS 4. Bone florescent for complicated cases Hormonal Tests 1. Estrogen receptors 2. Progesterone receptors 3. Ca Marker Hen2 4. Tumor Marker Ca In our study, surgical treatment was done in two ways: 1. radical mastectomy and 2. Pan-radical mastectomy along with Hormonal or Radio therapy depending on histopathology and TNM criteria for tumor classification.